Group Exhibition-rs Aevi Collection, Museum of Contemporary Art - Antoniou, Klitsa (My University, 2026)
Ars Aevi Collection, Museum of Contemporary Art, Sarajevo. Bosnia Herzegovina Curated by Ibrahim Spahich